(untitled) (Conference Zone, 2022)
Unlike other, especially European countries in the past, women in the east occupied a special position in society. With the development of folds, with the development of speech, such abilities of women as writing, praise, acquire a stable epithet. Many sources are silent about the role of women in life, including their education. But in this study, despite the presence of a very small amount of information, an attempt was made to highlight the scientific significance of this process by studying the history of education and upbringing of women of the peoples of Central Asia since ancient times.